Implementation of Islamic Educational Values Based on Habituation in Improving Students' Discipline at SMP Negeri 2 Tinambung, Polman Regency - Ulfa; Firman; Muhammad Qadaruddin; Agus Muchsin; Muh Akib (Universitas Muhammadiyah Palu, 2024)
This result aims to reveal the implementation of Islamic educational values based on habituation in improving students' discipline at SMP Negeri 2 Tinambung, with sub-focuses including (1) the implementation of Islamic educational values based on habituation in improving students' discipline at SMP Negeri 2 Tinambung, (2) the results of the implementation of Islamic educational values based on habituation in improving students' discipline at SMP Negeri 2 Tinambung, (3) obstacles and solutions in the implementation of Islamic educational values based on habituation in improving students' discipline at SMP Negeri 2 Tinambung. This research uses a qualitative method by conducting a descriptive approach, and data validity is checked through triangulation and reference materials. The research informants include the school principal, Islamic education teacher, and students. The results of this research indicate that: (1) the implementation of Islamic educational values based on habituation in improving students' discipline at SMP Negeri 2 Tinambung, Polman Regency, includes habituation in morality, habituation in worship, and habituation in creed. (2) The results of the implementation of Islamic educational values based on habituation in improving students' discipline at SMP Negeri 2 Tinambung, Polman Regency, show the achievement of students' discipline in adhering to habits in SMP Negeri 2 Tinambung. This has successfully encouraged students to habitually follow the school rules, especially arriving at school on time, praying before starting learning, and leaving according to the specified schedule. (3) Obstacles and solutions in the implementation of Islamic educational values based on habituation in improving students' discipline at SMP Negeri 2 Tinambung include obstacles in external factors, internal factors, and social factors. The solution is for teachers to always set an example for students, and parents continue to advise and remind them to maintain discipline wherever they are.